2019
DOI: 10.2147/ott.s216355
|View full text |Cite
|
Sign up to set email alerts
|

<p>Tumor-Associated Macrophages (TAMs): A Critical Activator In Ovarian Cancer Metastasis</p>

Abstract: Tumor-associated macrophages (TAMs) that appear in every stage of cancer progression are usually tumor-promoting cells and are present abundantly in the tumor-associated microenvironment. In ovarian cancer, the overall and intratumoral M1/M2 ratio is a relatively efficient TAM parameter for predicting the prognosis of patients, especially for serous tissue type cancer. TAMs exhibit immunological checkpoint modulators, such as the B7 family and programmed death-ligand 1 (PD-L1), and play a key role in the devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(59 citation statements)
references
References 160 publications
(147 reference statements)
2
57
0
Order By: Relevance
“…The ascites samples actually do not show an up-regulation of LOX-5-derived products, which have been made responsible for tumor-promoting effects of neutrophils [68], but show increased levels of LOX and COX-products associated with the resolution of inflammation. Microparticles containing 14-HDoHE and 17-HDoHE and shedded from neutrophils may inhibit the pro-inflammatory action of activated macrophages [70], which have been demonstrated to promote tumor growth and metastasis [54]. The present in vitro studies with neutrophils isolated from healthy donors demonstrate that stimulation via NOX or via calcium release causes substantially different effector functions in neutrophils.…”
Section: ) Modulation Of the Adaptive Immune System By Netosis Promomentioning
confidence: 66%
See 1 more Smart Citation
“…The ascites samples actually do not show an up-regulation of LOX-5-derived products, which have been made responsible for tumor-promoting effects of neutrophils [68], but show increased levels of LOX and COX-products associated with the resolution of inflammation. Microparticles containing 14-HDoHE and 17-HDoHE and shedded from neutrophils may inhibit the pro-inflammatory action of activated macrophages [70], which have been demonstrated to promote tumor growth and metastasis [54]. The present in vitro studies with neutrophils isolated from healthy donors demonstrate that stimulation via NOX or via calcium release causes substantially different effector functions in neutrophils.…”
Section: ) Modulation Of the Adaptive Immune System By Netosis Promomentioning
confidence: 66%
“…Here, with regard to HGSOC we have collected ample evidence for NETosis associated with non-miliary tumor spread. NETosis as well as the activity of tumor-associated macrophages have been rather linked to the promotion of metastasis [53,54]. While non-miliary tumor spread is indeed characterized by more invasive growth, it is associated with better overall survival.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are several immunosuppressive mechanisms in the ovarian TME that limit the function of T cells, including T REG cells, MDSCs, and tumor‐associated Mϕs (TAMs) cancer‐associated fibroblasts, endothelial cells, adipocytes and the cancer cells themselves 75–77 ( Figure 2 ). Local inflammation promotes the secretion of prostaglandins that directly inhibit CD8 T cell function in solid cancers 78 .…”
Section: Ovarian Cancermentioning
confidence: 99%
“…Treg cells may inhibit tumor‐specific responses in the ovarian TME using a number of mechanisms, including the production of suppressive cytokines, such as IL‐10 and TGF‐β, that reduce the killing capacity of CD8 T cells. MDSCs and TAMs can also secrete suppressive cytokines and they can suppress T cell activation by engaging the inhibitory molecules 76,77 . Cumulatively, these cells create a local environment of chronic inflammation with high IL‐6 and TNF that inhibit T cell function, 80,81 alongside other suppressive mechanisms.…”
Section: Ovarian Cancermentioning
confidence: 99%
“…In addition to their role in both innate and adaptive immunity, research has shown that macrophages also play a dynamic role in the body by interacting with immune cells and epithelial cells to regulate the cellular environment through secretion of cytokines and chemokines [1][2][3][4]. Furthermore, studies on various cancers have revealed that macrophages participate in tumor initiation and development, especially the M2 subtype of macrophages [5][6][7][8][9][10]. A comprehensive understanding of macrophage polarization/subtypes and their function in cellular signaling will not only advance our current knowledge on these multifaceted macrophages but also shed light on how to target them for a cancer therapy purpose.…”
Section: Introductionmentioning
confidence: 99%